Business English Lingua Franca in intercultural (business) communication - Kankaanranta, Anne (Language at Work - Bridging Theory and Practice, 2008)
Typically, the term intercultural is used as a synonym for international in the sense that it is used to refer to communication taking place between people with international backgrounds. Thus, a different cultural background equals to a different national background, which suggests that the communicators do not share the same mother tongue. In such situations the communicators basically have two options: first, one party can switch over to the other party’s mother tongue; and second, both can use a common language which is neither party’s native tongue. Both options call for intercultural communication.